STRATEGI PERPUSTAKAAN PERGURUAN TINGGI DALAM MENINGKATKAN MINAT BACA SEBAGAI UPAYA MENGANTISIPASI HOAX (STUDI KASUS DI PERPUSTAKAAN UNIVERSITAS SEBELAS MARET SURAKARTA) - Utari, Sri (BACA: Jurnal Dokumentasi dan Informasi, 2018)
This paper discusses how the role of university libraries in increasing reading interest as an effort to anticipates hoax with case studies at Sebelas Maret University Library. The aim of the study is to determine the library strategies in increasing reading interest as an effort to combat hoaxes. This study uses qualitative methods with data collection participatory observation and documentation. The conclusion of this study is the strategy adopted by the Sebelas Maret Univercity Library in increasing reading interest is by holding various talk show activities, book fairs, writing seminars and workshops, information literacy, receiving student visits and students, applying excellent and superior services, providing various kinds library collections, and promotions and improvement of library infrastructure facilities. These various efforts are expected that the public's interest in reading will increase so that the public will not easily accept hoax information.